The differences in production of Holstein Friesian and Holstein Friesian x Norwegian Red F1 crossbreeds - Benak, Stipo, agronom; Bobić, Tina; Bilandžija, Katarina; Steiner, Zvonimir; Aračić, Ana; Gregić, Maja; Eman, Domagoj; Gantner, Vesna (2020)
The aim of this study was to compare the production, health and fertility traits of Holstein Friesian (HF) and their F1 crosses with Norwegian Red cows (HF x NRF F1). Only the production data’s from finished first lactations of the total 57 HF x NRF F1 crosses and 401 HF cows, and for health and fertility traits of 120 HF x NRF F1 crosses and 255 HF cows, were used. The differences in production traits were tested by a least square means using the GLM procedure in SAS. The milk yield in both lactation (standard 305 days and full lactation) were higher in HF x NRF F1 crosses for approximately 400 kg, but without significance. The differences in production traits (fat and protein (kg and %)) were significant (p<0.001; p<0.05) with higher values for HF x NRF F1 crosses comparing to HF cows, with exception of protein in full lactation. Regarding the fertility traits, HF x NRF F1 crosses had a better conception rate (+1.58 %), a lower number of the insemination per pregnancy (-0.43) and a shorter duration of the service period (-22.2) comparable to HF cows. F1 crosses had better health traits (with except for hoofs problem) comparing to HF cows, they had less cows with mastitis (-11.9 %), ketosis (-0.5 %), retained placenta (-4.8 %) and dislocation of the abomasum (-1.0 %), respectively. Because of the fact that all results were obtained on the basis of data from the first lactation cows, it is necessary to do more analyses of all studied traits in subsequent lactations, in order to get a much clearer insight into the studied issues.
Cilj rada bio je usporediti proizvodna, zdravstvena i svojstava plodnosti krava Holstein Friesian (HF) pasmine i njegovih F1 križanaca sa Norwegian Red pasminom krava (HF x NRF F1). Za potrebe ovoga istraživanja korišteni su samo proizvodni podaci zaključenih prvih laktacija za ukupno 57 HF x NRF F1 križanaca i 401 HF krava, te za zdravstvena i svojstva plodnosti za 120 HF x NRF F1 križanaca i 255 HF krava. Značajnost razlika u proizvodnim svojstvima testirana je analizom varijance uporabom PROC GLM procedure u SAS-u. Proizvodnja mlijeka u obje laktacije (standardna 305 dana i puna laktacija) bila je veća kod HF x NRF F1 križanaca za približno 400 kg, ali bez utvrđene značajnosti. Proizvodna svojstva (mast i protein (kg i %)) izuzevši protein u punoj laktaciji, bili su značajno veći (p<0,001; p<0,05) kod HF x NRF F1 križanaca u usporedbi sa HF kravama. Gledajući svojstva plodnosti, HF x NRF F1 križanci su imali bolju koncepciju (+1,58 %), manji broj osjemenjivanja krava po uspješnoj bređosti (-0,43), te kraće trajanje servisnog razdoblja (-22,2) u usporedbi sa HF kravama. HF x NRF F1 križanci su imala bolja zdravstvena svojstva (izuzev problema sa papcima) komparabilno sa HF kravama, odnosno imali su manje krava s mastitisom (-11,9 %), ketozom (-0,5 %), zaostalom posteljicom (-4,8 %), te dislokacijom sirišta (-1,0 %). Obzirom da su rezultati dobiveni od krava sa završenom prvom laktacijom, potrebno je analizirati i podatke od narednih laktacija, kako bi se dobio puno jasniji uvid u istraživanu problematiku.
Bibliografija: 22 jed.
Summary ; Sažetak.
Keywords: Mliječne krave -- Holstein Friesian -- Norwegian Red -- Proizvodna svojstva -- Zdravstvena svojstva -- Plodnost